Antibiotic Action, Drug Delivery, Biodegradability, and Wound Regeneration Characteristics of Surgical Sutures and Cutting-Edge Surgical Suture Manufacturing Technologies - Hye-Ree Han (Journal of Functional Biomaterials)
(1) Background: With the emergence of various super bacteria, interest in antibacterial properties, drug delivery, and wound regeneration is increasing in the field of surgical materials. There are many studies on surgical sutures, but not many recent ones that have studied structurally subdivided functions. Accordingly, various studies on surgical sutures were classified based on the main functions that are considered important, and studies were conducted by categorizing the latest production technology into 3D printing and electrospinning. (2) Methods: Data from the literature (n = 1077) were collected from databases such as PubMed, Harvard.edu, MDPI, Google Scholar, Web of Science, ACS, Nature, and IOP Publishing. The selected 103 papers were divided into two main groups: cutting-edge characteristics of surgical sutures and the latest technologies for manufacturing surgical sutures. (3) Results: Cutting-edge characteristics of surgical sutures were divided into four major categories: antibacterial, drug delivery, biodegradability, and wound regeneration, and examined in depth. In addition, the final technologies for manufacturing surgical sutures were divided into electrospinning and 3D printing. (4) Conclusions: The results of this study can contribute to the development of multifunctional surgical sutures that promote wound regeneration through antibacterial properties, drug elution, and biodegradability.